Simulation of bulk phases formed by polyphilic liquid crystal dendrimers - J.M. Ilnytskyi; J.S. Lintuvuori; M.R. Wilson (Condensed Matter Physics, 2010)
A coarse-grained simulation model for a third generation liquid crystalline dendrimer (LCDr) is presented. It allows, for the first time, for a successful molecular simulation study of a relation between the shape of a polyphilic macromolecular mesogen and the symmetry of a macroscopic phase. The model dendrimer consists of a soft central sphere and 32 grafted chains each terminated by a mesogen group. The mesogenic pair interactions are modelled by the recently proposed soft core spherocylinder model of Lintuvuori and Wilson [J. Chem. Phys, 128, 044906, (2008)]. Coarse-grained (CG) molecular dynamics (MD) simulations are performed on a melt of 100 molecules in the anisotropic-isobaric ensemble. The model LCDr shows conformational bistability, with both rod-like and disc-like conformations stable at lower temperatures. Each conformation can be induced by an external aligning field of appropriate symmetry that acts on the mesogens (uniaxial for rod-like and planar for disc-like), leading to formation of a monodomain smectic A (SmA) or a columnar (Col) phase, respectively. Both phases are stable for approximately the same temperature range and both exhibit a sharp transition to an isotropic cubic-like phase upon heating. We observe a very strong coupling between the conformation of the LCDr and the symmetry of a bulk phase, as suggested previously by theory. The study reveals rich potential in terms of the application of this form of CG modelling to the study of molecular self-assembly of liquid crystalline macromolecules.